2022
DOI: 10.1038/s41467-022-31903-2
|View full text |Cite
|
Sign up to set email alerts
|

Coupled influence of tectonics, climate, and surface processes on landscape evolution in southwestern North America

Abstract: The Cenozoic landscape evolution in southwestern North America is ascribed to crustal isostasy, dynamic topography, or lithosphere tectonics, but their relative contributions remain controversial. Here we reconstruct landscape history since the late Eocene by investigating the interplay between mantle convection, lithosphere dynamics, climate, and surface processes using fully coupled four-dimensional numerical models. Our quantified depth-dependent strain rate and stress history within the lithosphere, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 108 publications
(201 reference statements)
1
21
0
Order By: Relevance
“…Our models cannot reproduce absolute topography since surface processes (e.g., erosion and sedimentation), isostatic adjustment, and mantle flow‐related dynamics are not included. All these factors could exert impacts on absolute topography and may lead to lateral variations in elevation (Bahadori et al., 2022; Faccenna & Becker, 2010; Wolf et al., 2022), but they cannot simultaneously explain the more prominent uplift and corresponding more significant shortening of the northern plateau than the central plateau. The far‐field compression associated with the Arabia‐Eurasia collision should be the dominant factor.…”
Section: Model Configurationmentioning
confidence: 99%
“…Our models cannot reproduce absolute topography since surface processes (e.g., erosion and sedimentation), isostatic adjustment, and mantle flow‐related dynamics are not included. All these factors could exert impacts on absolute topography and may lead to lateral variations in elevation (Bahadori et al., 2022; Faccenna & Becker, 2010; Wolf et al., 2022), but they cannot simultaneously explain the more prominent uplift and corresponding more significant shortening of the northern plateau than the central plateau. The far‐field compression associated with the Arabia‐Eurasia collision should be the dominant factor.…”
Section: Model Configurationmentioning
confidence: 99%
“…The paleotopographic evolution of the southern Rocky Mountains is enigmatic because they currently are anomalously high given their location far from an active plate boundary (Bahadori et al., 2022; Lipman et al., 1973). We focus here on several sites in the San Juan Volcanic Field (SJVF, Figure 1) of the southern Rocky Mountains of CO, USA.…”
Section: San Juan Volcanic Field Case Studymentioning
confidence: 99%
“…1 ). Recent numerical modeling efforts 39 , 40 have shown that the crustal extension and topographic collapse in SWNA was caused by tensional deviatoric stresses associated with high gravitational potential energy (GPE) of this mountain chain, as plate motion boundary conditions transitioned from subduction to transform motion and as the lithosphere was progressively weakened by heat, fluids, and volcanism during the slab rollback history 39 , 40 . The proximity of restored locations of MCCs along the chain of high paleo-topography 37 (Fig.…”
Section: Introductionmentioning
confidence: 99%